The incredible shrinking squad! - Rosen, Lucy (Marvel super hero squad (LB Kids (Firm)), 2012)
Ant Man, Wasp and Spider-man catch Enchantress and MODOK in the act of robbing a jewelry store, but during the villains' efforts to escape, Enchantress drops the jewels into the zoo and the squad scrambles to find them all.